Implementasi Pencarian Rute Terpendek Tour Wisata di Banyuwangi pada Agen Travel Menggunakan Algoritma Floyd Warshall - Kusbudiono; Vira Ulyatul Maghfiroh; Ikhsanul Halikin; Kristiana Wijaya (Program Studi Matematika Universitas Negeri Jakarta, 2023)
Tourism is travel aim to visit tourist attractions. Holidays to tourist attractions can eliminate boredom, improve the brain's work system, and foster a feeling of happiness. Holidays to tourist attractions can be assisted by travel agents. This research was carried out by looking for the shortest route from tour packages the travel agent in Banyuwangi. Search for the shortest route is aim to save time on travel package rundown tour, the distance traveled, and the fuel used. Search for the shortest route can be calculated using Floyd Warshall Algorithm. This algorithm was chosen because it can evaluate each pair vertex at each iteration to find the shortest distance. Search for the shortest distance is checking each pair vertex and choosing the smallest distance between the actual distance and the initial distance plus the final distance. The results of this research are found in the last iteration of each tour package. The total distance of the tour package is calculated using the Floyd Warshall Algorithm to get smaller distance than the total distance of the tour package with the route taken normally. Tour package distance using Floyd Warshall Algorithm experienced distance savings seen from the difference between the two.